Radiofrequency Catheter Ablation of Supraventricular Tachycardia in Patients With Pulmonary Hypertension: Feasibility and Long-Term Outcome - Zhou, Bin; Zhu, Yong-Jian; Zhai, Zheng-Qin; Weng, Si-Xian; Ma, Ya-Zhe; Yu, Feng-Yuan; Qi, Ying-Jie; Jiang, Yi-Zhou; Gao, Xin; Xu, Xi-Qi; Jiang, Xin; Jing, Zhi-Cheng; et al. (Frontiers in Physiology, 2021)
Background Supraventricular tachycardia (SVT) occurs commonly and is strongly correlated with clinical deterioration in patients with pulmonary hypertension (PH). This study aimed to investigate the feasibility and long-term outcome of radiofrequency catheter ablation (RFCA) in PH patients with SVT. Materials and Methods Consecutive PH patients with SVT who were scheduled to undergo electrophysiological study and RFCA between September 2010 and July 2019 were included. The acute results and long-term success of RFCA were assessed after the procedure. Results In total, 71 PH patients with 76 episodes of SVT were analyzed. Cavotricuspid isthmus-dependent atrial flutter (n = 33, 43.5%) was the most common SVT type, followed by atrioventricular nodal reentrant tachycardia (n = 16, 21.1%). Of the 71 patients, 60 (84.5%) underwent successful electrophysiological study and were subsequently treated by RFCA. Among them, acute sinus rhythm was restored in 54 (90.0%) patients, and procedure-related complications were observed in 4 (6.7%) patients. Univariate logistic regression analysis showed that cavotricuspid isthmus-independent atrial flutter [odds ratio (OR) 25.00, 95% confidence interval (CI) 3.45–180.98, p = 0.001] and wider pulmonary artery diameter (OR 1.19, 95% CI 1.03–1.38; p = 0.016) were associated with RFCA failure. During a median follow-up of 36 (range, 3–108) months, 7 patients with atrial flutter experienced recurrence, yielding a 78.3% 3-year success rate for RFCA treatment. Conclusion The findings suggest that RFCA of SVT in PH patients is feasible and has a good long-term success rate. Cavotricuspid isthmus-independent atrial flutter and a wider PAD could increase the risk for ablation failure.